Penerapan Konseling Islam Dengan Teknik Modelling Dalam Mengatasi Al-annanah Pada Penerima Manfaat Penyandang Disabilitas - Dila Julianti; Abdur Razzaq; Lena Marianti (Scidacplus, 2023)
Al-annanah is often faced by individuals with disabilities, which can affect their psychological well-being and quality of life. The application of Islamic counseling will provide a strong framework of values ​​and principles in guiding participants in understanding and overcoming their al-annanah with a view that is in accordance with Islamic teachings. This research is entitled